On a Tightrope - Lom, Petr (Norway : Grude, Torstein, 2007)
In an orphanage in the Chinese province of Xinjiang, children study tightrope walking. The children are Uyghurs, the largest Muslim minority in China. Fearing the Uyghurs' separatist movement, China rules with an iron fist in Xinjiang. Youngsters are forbidden from professing their religion, and the regime jumps at every opportunity to glorify the unity of China. Walking the tightrope is an age-old Uyghur tradition, and their feats are spectacular. The children look up to their coach, but his intentions are dubious. After nine months of intense training, most children are told they have failed and will not be able to continue the course. Petr Lom follows four children in the orphanage in their struggle to build a better life for themselves. They talk about the frustration of having to practise so hard, only to find out that it was all for nothing. But they also discuss their life in the orphanage and the required loyalty to Communism, and their dreams for the future come up on a regular basis. Though not all of them really want a career in tightrope walking, they still feel that they have failed. Then, an elderly retired tightrope walker shows up and becomes their new coach. Lovingly and patiently, he teaches the children to walk the tightrope, this time with success.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films